Toxoplasmose canina: Aspectos clínicos e patológicos - Bresciani, Katia Denise Saraiva [UNESP]; Da Costa, Alvimar José [UNESP]; Navarro, Italmar Teodorico; Toniollo, Gilson Hélio [UNESP]; Sakamoto, Cláudio Alessandro Massamitsu [UNESP]; Arantes, Tiago Pereira [UNESP]; Gennari, Solange Maria (Universidade Estadual de Londrina, 2008)
Inquiries about toxoplasmosis are essential because its zoonotic potential and pathogenicity in pets and production animals. The dog can be involved in the mechanical transmission of the infection by Toxoplasma gondii and in spite of not being the definitive host, it has an epidemiological role in this disease. The high rate of dogs naturally infected by T. gondii and the great possibility of adquiring this protozoan, justify the importance of attempting against for the occurrence of this illness. The aim of this article was to demonstrated through literature revision, some clinical aspects, epidemic and pathological of the toxoplasmosis in the canine species.
Canine toxoplasmosis : CCCClinical and pathological aspects
Keywords: Dogs; Toxoplasma gondii